Childhood cancer and drugs in pregnancy. Issue 6165 (17th March 1979) - Sanders, B M; Draper, G J
Abstract : A study was carried out on 11 169 matched case-control pairs of children aged up to 15 years included in the Oxford Survey of Childhood Cancers to see whether an association exists between cancer in children and drugs given to their mothers during pregnancy. The mothers of children who developed cancer reported about 25% more illnesses during pregnancy than mothers of healthy control children. Two specific illnesses, pulmonary tuberculosis and epilepsy, were investigated. For these there was a higher than average case-control excess of reports and there had been a suggestion that the drugs used in treatment, isoniazid and phenytoin, might be carcinogenic. The results of this investigation provide no real evidence for any association between the drugs taken by the mothers during pregnancy and subsequent cancer in the child.